Olej, kapusta, kalosze. Inteligencja i głupota w polskich i bułgarskich związkach frazeologicznych - Denczewa, Diliana (Postscriptum Polonistyczne, 2020)
The article discusses the conceptualization of intelligence and stupidity in Polish and Bulgarian phrases. The research found out a regularity with which both languages employ the same metaphors for designation the above mentioned human qualities. They are based on similar conceptual domains, organizing similar human experience. Intelligence in both languages is conceptualized as instrument (razor), stupidity as domestic animal (cow, goose) or very simple foodstuffs (cabbage, beans). The differences in conceptualizing of the intelligence and stupidity in both Slavic languages are insignificant.